Tax shelters and corporate debt policy - Graham, John R.; Tucker, Alan L. (Journal of Financial Economics, 2006)
We gather a unique sample of 44 tax shelter cases to investigate the magnitude of tax shelter activity and whether participating in a shelter is related to corporate debt policy. The average annual deduction produced by the shelters in our sample is very large, equaling approximately nine percent of asset value. These deductions are more than three times as large as interest deductions for comparable companies. The firms in our sample use less debt when they engage in tax sheltering. Compared to companies with similar pre-shelter debt ratios, the debt ratios of firms engaged in tax shelters fall by about 8%. The tax shelter firms in our sample appear underlevered if shelters are ignored but do not appear underlevered once shelters are considered.